Oxygen-enhanced MRI MOLLI T1 mapping during chemoradiotherapy in anal squamous cell carcinoma - Bluemke, E; Bulte, D; Bertrand, A; George, B; Cooke, R; Chu, K-Y; Durrant, L; Goh, V; Jacobs, C; Ng, SM; Strauss, VY; Hawkins, MA; et al. (Elsevier, 2020)
Background and Purpose: Oxygen-enhanced magnetic resonance imaging (MRI) and T1-mapping was used to explore its effectiveness as a prognostic imaging biomarker for chemoradiotherapy outcome in anal squamous cell carcinoma.